PENGARUH MORAL PAJAK, BUDAYA PAJAK DAN TARIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN DI KPP PRATAMA BADUNG UTARA - Komang Sani Asih; I Ketut Yudana Adi (Journal Research of Accounting, 2020)
This study aims to determine tax morale, tax culture and tax rates on corporate taxpayer compliance in KPP Pratama Badung Utara both partially and simultaneously, the number of taxpayers used as 40 research samples, the data used in this study is primary data distributed through questionnaires. The results showed that the sig value of the tax moral variable (X1) was 0.002 <0.05 tax culture variable (X2) of 0.022 <0.05 and the tax rate variable (X3) was 0.003 <0.05 and the sig F value was 0.000 < 0.05 so that it can be concluded partially and simultaneously the variables of tax moral, tax culture and tax rates affect the taxpayer compliance in the KPP Pratama Badung Utara. The value of the coefficient of determination (R Square) of 0.561 means that 56.1% of corporate taxpayer compliance in KPP Pratama Badung Utara is influenced by tax morale, tax culture and tax rates while the remaining 43.9% is influenced by other variables outside of this study.